The dynamics of the general practitioner-nephrologist collaboration for the management of patients with chronic kidney disease before and after dialysis initiation: a mixed-methods study - Maxime Raffray; Cécile Vigneau; Cécile Couchoud; Laetitia Laude; Arnaud Campéon; François-Xavier Schweyer; Sahar Bayat (SAGE Publishing, 2022)
Background: Effective collaboration between general practitioners (GP) and nephrologists is crucial in CKD care. We aimed to analyse GPs' and nephrologists' presence and involvement in CKD care and assess how they intertwine to shape patients' trajectories. Methods: We conducted a mixed-methods study that included all patients with CKD who started dialysis in France in 2015 (the REIN registry) and a sample of nephrologists and GPs. We quantified professionals' presence through patients' reimbursed healthcare from the French National Health Data System, 2 years before and 1 year after dialysis start. Involvement in CKD care was derived from the nephrologists' and GPs' interviews. Results: Among 8856 patients included, nephrologists' presence progressively increased from 29% to 67% of patients with a contact during the 2 years before dialysis start. However, this was partly dependent on the GPs' referral practices. Interviews revealed that GPs initially controlled the therapeutic strategy on their own. Although unease grew with CKD's management complexity, reducing their involvement in favour of nephrologists, GPs' presence remained frequent throughout the pre-dialysis period. Upon dialysis start, nephrologists' presence and involvement became total, while GPs' greatly decreased (48% of patients with a contact at month 12 after dialysis start). Collaboration was smooth when GPs maintained contact with patients and could contribute to their care through aspects of their specialty they valued. Conclusions: This mixed-methods study shows presences and forms of involvement of GPs and nephrologists in CKD care adjusting along the course of CKD and unveils the mechanisms at play in their collaboration.